2021
DOI: 10.1111/hdi.12981
|View full text |Cite
|
Sign up to set email alerts
|

Utility of TG/HDL‐c ratio as a predictor of mortality and cardiovascular disease in patients with chronic kidney disease undergoing hemodialysis: A systematic review

Abstract: The triglyceride/high-density cholesterol-lipoprotein (TG/HDL-c) is a biomarker of cardiovascular events and mortality. In hemodialysis patients, the evidence is controversial. A systematic review was carried out in the Medline, Scopus, Embase, Web of Science, and Pubmed databases to identify the relevant cohort studies on cardiovascular events and mortality in hemodialysis patients the role of TG/HDL-c as a risk factor. Four cohort-type studies were evaluated, with a total of 52,579 hemodialysis patients. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Previous studies have demonstrated the correlation of lipid parameters including TG, TC, HDL-C, LDL-C, LDL-C/HDL-C, non-HDL-C, TC/HDL-C with pre-DM and DM [ 28 31 ]. Among them, TG and HDL-C have been considered important risk factors for developing CVD in Asians [ 32 , 33 ]. The potential clinical significance of TG/HDL-C has been widely explored as a product of these two.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the correlation of lipid parameters including TG, TC, HDL-C, LDL-C, LDL-C/HDL-C, non-HDL-C, TC/HDL-C with pre-DM and DM [ 28 31 ]. Among them, TG and HDL-C have been considered important risk factors for developing CVD in Asians [ 32 , 33 ]. The potential clinical significance of TG/HDL-C has been widely explored as a product of these two.…”
Section: Discussionmentioning
confidence: 99%
“…A large retrospective analysis of 50 673 American HD patients found that the TG/HDL-C ratio is a protective factor for mortality 36. Gonzáles-Rubianes et al pointed out that three studies focused on the Asian HD population showed that a higher TG/HDL-C ratio was associated with higher mortality 37. A U-shaped relationship between atherogenic index of plasma (AIP, the logarithmic ratio of TG/HDL-C) and all-cause death in dialysis populations was discovered in a Korean study, with both the greatest and lowest AIP groups being related to high mortality 38.…”
Section: Discussionmentioning
confidence: 99%
“…36 Gonzáles-Rubianes et al pointed out that three studies focused on the Asian HD population showed that a higher TG/HDL-C ratio was associated with higher mortality. 37 A U-shaped relationship between atherogenic index of plasma (AIP, the logarithmic ratio of TG/ HDL-C) and all-cause death in dialysis populations was discovered in a Korean study, with both the greatest and lowest AIP groups being related to high mortality. 38 A study focused on Taiwan patients reported that high TG/ HDL-C levels were related to worse CV events and death in dialysis populations, but the association did not exist in diabetic dialysis patients.…”
Section: The Utility and Implications Of The Tg/hdl-c Ratiomentioning
confidence: 99%
“…Previous studies have demonstrated the correlation of lipid parameters including TG, TC, HDL-C, LDL-C, LDL-C/HDL-C, non-HDL-C, TC/HDL-C with pre-DM and DM [27][28][29][30]. Among them, TG and HDL-C have been considered as important risk factors for the development of cardiovascular disease (CVD) in Asians [31][32].…”
Section: Discussionmentioning
confidence: 99%